Java Islam: Relationship of Javanese Culture and Islamic Mystism in The Post-Colonial Study Perspective - Rubaidi, Rubaidi (el Harakah: Jurnal Budaya Islam, 2019)
This paper examines and shows at the same time about Javanese Islam (Islam Nusantara) which is typical of a few Muslims in the world. The characteristic in question is a combination of Javanese culture (Javanese original religion, Hindu and Buddhist) with the intrinsic dimension of Islam itself. This combination occurs because it is bound by a red thread called mysticism, which is between Javanese mysticism and Islamic mysticism as a compound. The two conception of mysticism is because the essence of mysticism actually contains the teachings of the unity (tauhid) of God. This encounter through mysticism allows for acculturation between Javanese culture and Islam. This thesis is based on the reconstruction of the thinking of Sufi teachers in the Majelis Shalawat Muhammad in Surabaya and Bojonegoro as a research base. The Sufi masters referred to were placed as sub-alternations which were prevalent in post-colonial studies. As a sub-altern, this paper is believed to better narrate the perpetrators of Islamic mysticism in understanding the dialectic between Islamic mysticism and original Javanese culture or Javanese mysticism itself. Their relations gave birth to what is called Javanese Islam which is typical in Indonesia. Makalah ini membahas dan menunjukkan pada saat yang sama tentang Islam Jawa (Islam Nusantara) yang merupakan ciri khas beberapa Muslim di dunia. Karakteristik yang dimaksud adalah kombinasi budaya Jawa (agama asli Jawa, Hindu dan Budha) dengan dimensi intrinsik Islam itu sendiri. Kombinasi ini terjadi karena diikat oleh benang merah yang disebut mistisisme, yaitu antara mistisisme Jawa dan mistisisme Islam yang merupakan senyawa. Dua konsepsi mistisisme adalah karena esensi mistisisme sebenarnya mengandung ajaran persatuan (tauhid) Tuhan. Pertemuan ini melalui mistisisme memungkinkan akulturasi antara budaya Jawa dan Islam. Tesis ini didasarkan pada rekonstruksi pemikiran guru sufi di Majelis Shalawat Muhammad di Surabaya dan Bojonegoro sebagai basis penelitian. Para guru sufi yang disebut ditempatkan sebagai sub-pergantian yang lazim dalam studi pasca-kolonial. Sebagai pengganti, makalah ini diyakini akan lebih baik menceritakan para pelaku mistisisme Islam dalam memahami dialektika antara mistisisme Islam dan budaya Jawa asli atau mistisisme Jawa itu sendiri. Hubungan mereka melahirkan apa yang disebut Islam Jawa yang khas di Indonesia.